A Survey On The Language Learning Strategies Used By The UHB 1412 Students - Abdul Samad, Adlina; Sakdev Singh, Salveen Kaur Gill (2010)
This study generally investigates the language learning strategy (LLS) used by UHB 1412 students. The study also attempts to identify the language learning strategy used by good and poor learners of English. The Oxford’s (1990) Strategy Inventory for Language Learning (SILL) was administered to hundred and four first year students with few modifications done in the questionnaires. The aspects that were examined entails the six language learning strategies classified by Oxford (1990) as cognitive strategies, memory strategies, compensation strategies, metacognitive strategies, affective strategies and social strategies. The data were then analysed using the Statistical Package for The Social Science (SPSS) version 12.00. The findings shows that the students attempted to use more metacognitive strategy and social strategy in their learning. In addition, the favoured language learning strategies used by good and poor learners were also identified. This study aims to equip students with the learning strategies they need in order to succeed in the learning of a second language. It is also hoped that the study could help both the language practitioners and experts in the field to consider the use of the six language learning strategies in achieving the goals of learning.